IMPROVING DIGITAL SHARIA FINANCIAL LITERACY AND INCLUSION FOR MERCHANT IN MURA TIGA VILLAGE, MULAK ULU DISTRICT, LAHAT REGENCY - Taufik, Taufik; Adam, Mohamad; Yusnaini, Yusnaini; Cahyadi, Afriyadi; Yulianita, Anna (Universitas Muhammadiyah Tapanuli Selatan, 2026)
The purpose of this community service activity is to enhance understanding of literacy, inclusion, and the digitalization of Islamic finance among merchants in Muara Tiga Village, Mulak Ulu District, Lahat Regency. The implementation method involved delivering presentations on the concepts, products, and operational systems of Islamic finance. This activity also introduced the use of the ByondBSI application and the SalamDigital platform from Bank Syariah Indonesia (BSI). The results of the activity showed a significant increase in participants' understanding of Islamic financial literacy and inclusion after attending the program. In addition, merchants' understanding of using the ByondBSI digital application and SalamDigital BSI platform improved considerably following their participation.